P56 Cross-sectional study of prevalence of sensitisation to mouse allergens in laboratory animal workers: the SPIRAL (Safe Practice In Reducing Allergy in Laboratories) study. (12th November 2015) - Feary, JR; Fitzgerald, B; Lightfoot, Z; Banya, W; Jones, M; Cullinan, P
Abstract : Introduction: At least 12000 people work with laboratory animals in the UK. Approximately 15% of exposed employees develop specific IgE sensitisation and 10% clinical symptoms of occupational rhinitis and asthma due to laboratory animal allergy (LAA). Individually ventilated cages (IVCs) are increasingly replacing conventional open cages (primarily for mice welfare); whilst this can be associated with lower levels of ambient aeroallergen levels no corresponding reduction in incidence of LAA is apparent. The SPIRAL (Safe Practice In Reducing Allergy in Laboratories) study is a large multi-centred study designed to increase understanding of the complex association between workplace exposure to mouse allergens and development of sensitisation, and to evaluate the risk of working with mice today. Methods: A cross-sectional study of animal workers at UK medical research institutions is underway. Primary outcome is a comparison of prevalence of sensitisation to mouse proteins in those working in IVC only and those working in mixed facilities (open cages +/- IVCs). Participants complete a detailed online questionnaire including questions about work tasks and practices. Skin-prick tests to common aeroallergens and various animal proteins are performed and blood samples analysed for serum specific IgE to Mus m 1 (mouse urinary protein) and mouse epithelium. Aeroallergen sampling for particulate matter and Mus m 1 is undertaken concurrently to provide objective exposure measurements (results presented elsewhere). Results: 507 participants have been recruited to date. Analyses were restricted to those with less than 5 years exposure to mice (n = 212); of these, 10 (5%) participants were sensitised to mouse proteins. Prevalence of sensitisation was 3.5% in IVC only facilities and 6.3% in open cage/mixed facilities. Although numbers are small, a history of atopy to common aeroallergens and the site at which people worked appears to be associated with risk of sensitisation. Reporting of symptoms of laboratory animal allergy was as anticipated. (Table 1 ). Conclusion: The results from the SPIRAL study will be used to develop an evidence-based "Code of best working practices" for facilities using IVC systems, nationally and further afield, with the overall goal of significantly reducing the incidence of LAA.